PENERAPAN ILMU TASAWUF DALAM MEMBENTUK AKHLAK MULIA DI PONDOK PESANTREN DARUL HADITS HUTA BARINGIN KECAMATAN SIABU KABUPATEN MANDAILING NATAL - Manahan Efendi (Yayasan Baitul Hikmah al-Zain, 2024)
The application of Sufism in forming noble morals is an approach based on spiritual and ethical values ​​in Islam. Sufism, or Sufism, is a branch of Islamic religious knowledge that focuses on inner aspects and spirituality, with the main aim of achieving closeness to Allah and forming a nobler character. The science of Sufism, in this case, contributes significantly in forming noble morals. This research aims to investigate the system of applying Sufism in forming noble morals at the Darul Hadits Huta Baringin Islamic Boarding School, Siabu District, Mandailing Natal Regency, as well as identifying factors that can support or hinder its application by students. A qualitative approach with data collection methods through observation, interviews and documentation is the approach used in this research. By combining observations, interviews and document analysis, this is able to achieve a more holistic understanding of the system of applying Sufism in forming noble morals. The results of this research show that it is still less effective in its implementation, because there is a barrier factor in the form of students' laziness in studying their lessons, especially in their application, and supporting factors can be applied in the form of a teacher's approach by explaining the importance of Sufism and the threat approach. The implementation of classroom management by teachers at the Darul Hadits Huta Baringin Islamic Boarding School is still less effective